A phase 1 study of vinblastine in combination with carboplatin for children with low-grade gliomas: a Children's Oncology Group phase 1 consortium study - Jakacki, Regina I. (Oxford University Press, 2011)
Both carboplatin and vinblastine have demonstrated single-agent activity in children with low-grade gliomas. A phase 1 trial evaluating 2 different schedules of these 2 agents in combination was performed: (1) Schedule A = carboplatin (140 mg/m(2)) weekly × 3 + vinblastine (4.5 or 3.5 mg/m(2)) weekly × 6, every 6 weeks; (2) Schedule B = carboplatin (300, 400, or 500 mg/m(2)) on day 1 + vinblastine (4.0 mg/m(2)) weekly × 3, every 4 weeks. Twenty-six patients, median (range) age 4.4 (0.7–14.8) years, were enrolled. Four of 9 patients enrolled on Schedule A had recurrent grade 4 neutropenia, suggesting that this schedule was not feasible. Seventeen patients were enrolled on Schedule B. At the 500 mg/m(2) carboplatin dose level, 2 of 3 patients developed dose-limiting toxicity (elevated alkaline phosphatase, neutropenia). At the 400 mg/m(2) carboplatin dose level, none of the 6 patients had dose-limiting toxicity. Ten of 16 patients who received treatment on Schedule B completed the prescribed 12 courses. Of the 21 patients evaluable for response, central review confirmed 1 partial response and 6 minor responses. Eleven patients had stable disease (>3 months) and 3 developed progressive disease. Seven of 9 patients with visual pathway tumors and acute visual changes prior to enrollment had documented improvement. The recommended phase 2 dose and schedule is carboplatin, 400 mg/m(2)/dose on day 1, and vinblastine, 4 mg/m(2)/dose, weekly × 3, repeated every 4 weeks. Further study of this regimen in patients with low-grade glioma is warranted.